Application research on the sensitivity of porous silicon. (September 2017) - Xu, Gaobin; Xi, Ye; Chen, Xing; Ma, Yuanming
Abstract: Applications based on sensitive property of porous silicon (PSi) were researched. As a kind of porous material, the feasibility of PSi as a getter material was studied. Five groups of samples with different parameters were prepared. The gas-sensing property of PSi was studied by the test system and suitable parameters of PSi were also discussed. Meanwhile a novel structure of humidity sensor, using porous silicon as humidity-sensitive material, based on MEMS process has been successfully designed. The humidity-sensing properties were studied by a test system. Because of the polysilicon layer deposited upon the PSi layer, the humidity sensor can realize a quick dehumidification by itself. To extend service life and reduce the effect of the environment, a passivation layer (Si3 N4 ) was also deposited on the surface of electrodes. The result indicated the novel humidity sensor presented high sensitivity (1.1 pF/RH%), low hysteresis, low temperature coefficient (0.5%RH/°C) and high stability.